The Representation of the two American candidates of the U.S. presidential elections 2016 in the world's newspapers: a critical discourse analysis - Donia Nagy Saeed Diab (Insights into Language, Culture and Communication)
The present study investigates the presentation of the two American candidates Donald Trump and Hillary Clinton in the presidential elections that occurred through the year 2016 in the world news.  The study aims at examining how the Critical Discourse Analysis (CDA) tools together with cognitive semantics tools are applied to highlight the representation of both candidates throughout the period of the elections (2016).  The study focuses on the framing technique as a tool of the cognitive semantics and highlights how the choice of words affects the idea of representing each candidate whether positively or negatively.